Sejahtera Leadership and Sustainable Development Goal (SDGs) - Murdipi, Rafiqa (Kulliyyah of Economics and Management Sciences International Islamic University Malaysia, 2021)
This article discusses the link between the leadership of Sejahtera and the Sustainable Development Goals (SDGs). Sejahtera Leadership may promote and act as a catalyst for accomplishing SDGs due to the factors that make up Sejahtera Leadership. Governance is important in determining the effectiveness and efficiency with which goals are achieved, and because leadership determines the quality of institutions, good leadership promotes good institutions, which can then be boosted to achieve the SDGs.